Self-Distancing Reduces Probability-Weighting Biases - Sun, Qingzhou; Zhang, Huanren; Sai, Liyang; Hu, Fengpei (Frontiers in Psychology, 2018)
We have abundant evidence that people exhibit biases in weighting probability information. The current study aims to examine whether self-distancing would reduce these biases. Participants in this study were instructed to use either a self-distancing or a self-immersing strategy to regulate their reasoning when they indicated their valuations of different lotteries. The results show that, compared to the baseline group, participants in the self-distancing group exhibited less distortion in the probability- weighting function, while those in the self-immersing group exhibited more distortion. These results offer evidence for the power of self-distancing in reducing probability- weighting biases.